OP0165 Whole-body MRI for assessment of enthesitis in psoriatic arthritis, axial spondyloarthritis and healthy subjects – a comparison with 7 clinical enthesitis indices. (23rd January 2014) - Poggenborg, R.P.; Eshed, I.; Pedersen, S.J.; Sørensen, I.J.; Madsen, O.R.; Møller, J.; Østergaard, M.
Abstract : Background: Tender entheses is a common disease manifestation in patients with psoriatic arthritis (PsA) and spondyloarthritis (SpA). Whole-body MRI (WBMRI) is a new imaging modality where patients are scanned from "head to toe" in one single scan. However, only few studies have investigated the ability of WBMRI to detect enthesitis in patients with PsA and SpA(1;2). Objectives: The aim of this pilot study was to gain insight into the potential usefulness of WBMRI for detection of enthesitis in patients with PsA and SpA. Methods: Patients with clinically active PsA, clinically active axial SpA and healthy subjects (HS) were included. All participants were examined for tenderness at 18 entheses (35 locations) included in the Berlin (3;4), Major (3;6), Gladman (5), Leeds (6), MASES (7), SPARCC (8) or IMPACT (9) enthesitis indices. The WBMRIs (3 tesla, T1 -weighted pre- and post-contrast and STIR sequences with coronal orientation, slice thickness 4-6 mm) were anonymized and evaluated by an experienced musculoskeletal radiologist (IE). Enthesitis was scored as present, absent or not possible to evaluate. Results: The PsA (n=20)/SpA (n=20)/HS (n=13) had a BASDAI of median (range) 48 (9-85)/54 (2-93)/2 (0-13) mm and DAS28: 4.35 (2.38-6.29)/3.38 (1.46-4.79)/NA. Evaluation of entheses on WBMRI was most often possible at the anterior superior iliac spine (94% of the 104 entheses), iliac crest (94%), and greater trochanter (GT) (92%), while evaluation was rarely possible at the insertion of plantar fascia into calcaneus (0%), 7th costochondral joint (2%), and patellar ligament at tibial tubercle (2%). Inflammation was frequently seen at GT (PsA/SpA: 64%/44%), Achilles tendon (36%/62%) and supraspinatus insertion on the humerus (SH) (28%/26%). There were no statistical significant associations between enthesitis on WBMRI and tender entheses assessed according to 7 enthesitis indices (see Table 1 ). On the level of the individual enthesis, the best agreement between clinical examination and MRI was found for the right ischial tuberosity (IT) (PsA/SpA: kappa 0.46; 0.40), left IT (SpA: 0.56), and left SH (SpA: 0.43). Conclusions: WBMRI is a new promising imaging modality for evaluation of entheses in patients with PsA and SpA. Future research should include optimization of image acquisition, e.g. positioning of hands and feet, slice thickness and slice orientation. References: Althoff, ARD 2007. Weckbach, EuJRad 2011. Braun, Lancet 2002. Gladman, J Rheum 2007. Gladman, J Rheum 2004. Healy, AR 2008. Heuft-Dorenbosch, ARD 2003. Maksymowych, ARD 2009. Antoni, ARD 2005 Disclosure of Interest: None Declared